2017
DOI: 10.1371/journal.pone.0187080
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving the evil eye: Investigating hostile interpretation of ambiguous facial emotional expression in violent and non-violent offenders

Abstract: Research into the causal and perpetuating factors influencing aggression has partly focused on the general tendency of aggression-prone individuals to infer hostile intent in others, even in ambiguous circumstances. This is referred to as the ‘hostile interpretation bias’. Whether this hostile interpretation bias also exists in basal information processing, such as perception of facial emotion, is not yet known, especially with respect to the perception of ambiguous expressions. In addition, little is known ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…To date, only a few studies have explored face-body integration processes, targeting only adult offenders. Most of these works have reported impaired facial emotion recognition and attentional biases towards angry body postures (Kret and de Gelder, 2013; Kuin et al, 2017). Violent offenders tend to exhibit a bias towards aggressive body language, including anger or disgust postures (Kret and de Gelder, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few studies have explored face-body integration processes, targeting only adult offenders. Most of these works have reported impaired facial emotion recognition and attentional biases towards angry body postures (Kret and de Gelder, 2013; Kuin et al, 2017). Violent offenders tend to exhibit a bias towards aggressive body language, including anger or disgust postures (Kret and de Gelder, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the absence of such a relationship can be found in two prior studies that showed no significant correlations between aspects of aggression and a hostile interpretation bias (Kuin et al, 2017;Schwenk et al, 2014). In one of these studies the same emotion recognition paradigm was applied as in the present study (Kuin et al, 2017).…”
Section: Changing Perception 16mentioning
confidence: 59%
“…Moreover, age differences may not only be relevant with respect to aggression, but also in relation to hostile perception of emotions. In fact, in a previous explorative study with the same emotion perception task, was found that the tendency for hostile interpretation of facial expressions declined with age (Kuin et al, 2017), which may imply that the bias could have been less pronounced in the present population than in that of the previous two studies to begin with (this is further elaborated on in the limitations section below).…”
Section: Changing Perception 16mentioning
confidence: 67%
“…Early research suggested that aggressive and anger-prone individuals tend to respond negatively in socially ambiguous situations (Barefoot et al, 1989;Dodge, 1980); however, research into how these individuals process and interpret facial expressions is mixed (Chapman et al, 2018;Kuin et al, 2017;Mellentin et al, 2015;Smeijers et al, 2017). Theories for the role of facial expressions in provoking aggression in anger-prone individuals are split and differentially emphasize bottom-up perceptual deficits in facial processing versus top-down cognitive biases (e.g., hostile attribution bias, social information processing).…”
Section: Aggressionmentioning
confidence: 99%